Analisis Penerapan Model Pembelajaran REACT (Relating, Experiencing, Applying, Cooperating, Transferring) dalam Meningkatkan Pemahaman Konsep Biologi: Analysis of the Application of the REACT (Relating, Experiencing, Applying, Cooperating, Transferring) Learning Model in Enhancing the Understanding of Biology Concepts - Lestari, Rina Diana (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This study aims to analyze the application of the REACT (Relating, Experiencing, Applying, Cooperating, Transferring) learning model in enhancing the understanding of biology concepts among senior high school students. The research employed a quasi-experimental method with a pretest-posttest control group design. The research population comprised eleventh-grade students of SMA Negeri 1 Surakarta, with a sample of 64 students divided into an experimental class and a control class. Data on concept understanding were collected using a reasoned multiple-choice test and were analyzed using an independent samples t-test and N-gain scores. The results showed that the application of the REACT model significantly improved students' understanding of biology concepts, yielding an N-gain score of 0.71 (high category), compared to conventional learning, which resulted in an N-gain score of 0.32 (medium category). The cooperating and transferring stages of the REACT model proved to be the most effective in helping students build a comprehensive understanding of the concepts. The study concludes that the REACT model is effective in enhancing students' understanding of biology concepts because it facilitates contextual and collaborative learning experiences and encourages students to transfer knowledge to new situations.